2017
DOI: 10.18632/oncotarget.22304
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic analysis in contrast-enhanced CT: predict treatment response to chemoradiotherapy in esophageal carcinoma

Abstract: ObjectivesTo investigate the capability of computed-tomography (CT) radiomic features to predict the therapeutic response of Esophageal Carcinoma (EC) to chemoradiotherapy (CRT).MethodsPretreatment contrast-enhanced CT images of 49 EC patients (33 responders, 16 nonresponders) who received with CRT were retrospectively analyzed. The region of tumor was contoured by two radiologists. A total of 214 features were extracted from the tumor region. Kruskal-Wallis test and receiver operating characteristic (ROC) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 37 publications
2
74
2
1
Order By: Relevance
“…The largest study in 49 patients found that histogram skewness, histogram kurtosis, GLSZM long-zone emphasis, and 2 Gabor transformed parameters MSA-54 and MSE-54, discriminated non-responders from responders using an artificial neural network-derived prediction model [35]. The two remaining studies have assessed prognostication.…”
Section: Ct Radiomicsmentioning
confidence: 99%
“…The largest study in 49 patients found that histogram skewness, histogram kurtosis, GLSZM long-zone emphasis, and 2 Gabor transformed parameters MSA-54 and MSE-54, discriminated non-responders from responders using an artificial neural network-derived prediction model [35]. The two remaining studies have assessed prognostication.…”
Section: Ct Radiomicsmentioning
confidence: 99%
“…Radiomics analysis has been associated with several clinical end points, several researchers showed that it has a potential to be developed into an imaging biomarker using different imaging modalities. We showed earlier that CT based radiomics has a potential in a variety of applications (11)(12)(13)(14)(15)(16)(17)(18)(19). Researchers also showed that it has promise using MR images for instance, Wibmer et al (33) and Vignti et al (34) showed the radiomics features as potential imaging biomarkers in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CT-derived radiomic texture features have shown promising prognostic value in a variety of cancer treatments. For instance, Hou et al performed radiomic analysis using contrast-enhanced CT and found that the identified radiomic features have the potential to predict treatment response in esophageal carcinoma with an AUC of 0.97 (11). Coroller et al showed that CT-based radiomics can be developed as a prognostic biomarker to predict distant metastasis in lung cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have reported the application of radiomics features in predicting the treatment response and prognosis for patients with esophageal cancer [10,13,14,[19][20][21][22] . Hou et al [22] extracted 214 radiomics features from the pretreatment enhanced CT images of 49 patients with esophageal cancer. A model based on 5 radiomics features was developed with an AUC of 0.686-0.727 and the classi cation accuracy is 0.891 and 0.972, respectively.…”
Section: Discussionmentioning
confidence: 99%